The Q-Space Deformed Wave Equation. (22nd July 2022) - Elamin, Mahjoub A.; Khalifa, Narjess Turki; Altoum, Sami H.
Abstract : Let q ∈ 0, 1 . We know that, when q tends to 1, we recover "classical" quantum mechanics. However, when q is not equal to one, we have a theory of quantum mechanics in a spacetime, i.e., a theory where the vacuum has a nonzero energy density. As a q -analogue on the space variable of the wave equation, we introduce the q -space wave equation. Solutions of these equations are given for q ∈ 0, 1 and for q ⟶ 0 . Since some states have more spin degrees of freedom than the physical particle has, the q -space wave equations remove the additional degrees of freedom.